The Evolutionary Conserved Transmembrane BAX Inhibitor Motif (TMBIM) Containing Protein Family Members 5 and 6 Are Essential for the Development and Survival of Drosophila melanogaster - Zhang, Li; Buhr, Sebastian; Voigt, Aaron; Methner, Axel (Frontiers in Cell and Developmental Biology, 2021)
The mammalian Transmembrane BAX Inhibitor Motif (TMBIM) protein family consists of six evolutionarily conserved hydrophobic proteins that affect programmed cell death and the regulation of intracellular calcium levels. The bacterial orthologue BsYetJ is a pH-dependent calcium channel. We here identified seven TMBIM family members in Drosophila melanogaster and describe their expression levels in diverse tissues and developmental stages. A phylogenetic analysis revealed that CG30379 represents the orthologue of human TMBIM4 although these two proteins are much less related than TMBIM5 (CG2076 and CG1287) and TMBIM6 (CG7188) with their respective orthologues. For TMBIM1-3 the assignment is more dubious because the fly and the human proteins cluster with each other. We focused our functional analysis on four family members based on expression levels and the availability of two RNAi lines. This revealed that the ubiquitous knockdown of CG3798 and CG3814 had no effect on development. Ubiquitous knockdown of dTmbim5 resulted in death at the pupa stage and knockdown of dTmbim6 in death mainly at the embryonic stage. Tissue-specific knockdown of dTmbim5 and 6 in muscle and neural tissue also greatly reduced lifespan through different mechanisms. Knockdown of the mitochondrial family member dTmbim5 resulted in reduced ATP production and a pro-apoptotic expression profile while knockdown of the ER protein dTmbim6 increased the ER calcium levels of neurons similar to the mammalian homologue. Our data demonstrate that TMBIM5 and 6 are essential for fly development and survival but, despite their shared protein structure, affect cell survival through different mechanisms.